2013
DOI: 10.1371/journal.pone.0071469
|View full text |Cite|
|
Sign up to set email alerts
|

Nurr1 Represses Tyrosine Hydroxylase Expression via SIRT1 in Human Neural Stem Cells

Abstract: Nurr1 is an orphan nuclear receptor best known for its essential role in the development and maintenance of midbrain dopaminergic (DA) neurons. During DA neurogenesis, Nurr1 directly targets human tyrosine hydroxylase (hTH). Here we investigated this targeting to identify the molecular mechanisms by which Nurr1 regulates DA neurogenesis. We previously cloned the hTH promoter and found three consensus elements for Nurr1 binding: NBRE-A, -B, and -C. In the present study, gel retardation and luciferase assays usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…A previous study in our laboratory demonstrated the benefits of applying nicotinamide as a differentiation agent to aid the conversion of stem cells to mature GABAergic neurons (18). Findings from this work and published literature (27)(28)(29) imply that this bioactive nutrient may also function as a catecholaminergic differentiation signal implicated in the development or maintenance of basal ganglia circuitry.…”
Section: Introductionmentioning
confidence: 55%
“…A previous study in our laboratory demonstrated the benefits of applying nicotinamide as a differentiation agent to aid the conversion of stem cells to mature GABAergic neurons (18). Findings from this work and published literature (27)(28)(29) imply that this bioactive nutrient may also function as a catecholaminergic differentiation signal implicated in the development or maintenance of basal ganglia circuitry.…”
Section: Introductionmentioning
confidence: 55%
“…A previous study in our laboratory demonstrated the benefits of applying nicotinamide as a differentiation agent to aid the conversion of stem cells to mature GABAergic neurons [ 18 ]. Findings from this work and published literature [ 27 29 ] imply that this bioactive nutrient may also function as a catecholaminergic differentiation signal implicated in the development or maintenance of basal ganglia circuitry.…”
Section: Introductionmentioning
confidence: 56%
“…Interestingly, transcriptional responses to Nurr1 appear to depend both on cell type and on the constitutive level of Nurr1 expression [17]. For example, Nurr1 strongly induces TH expression in rodent neural precursor and differentiated cells, but the inductive effects on TH in human neural precursor cells are more modest [18] and can even be repressive in human neural stem cells [19]. Such varying transcriptional responses to Nurr1 may depend on the constitutive level of protein expression.…”
Section: Discussionmentioning
confidence: 99%